Use of the Internet by Senior Secondary School Students in Ede North Local Government Area of Osun State, Nigeria - AJALA, BOLANLE ADEWUMI; OJOKUKU, BEATRICE YEMISI (MiddleBelt Journal of Library and Information Science, 2020)
The Internet has become a major instrument in the world of Information and Communication Technology, transforming the social world of both young and adults; influencing mode of communication, establishing, maintaining relationships and finding social support. This paper examines the use of the Internet by senior secondary school (SSS) students in Ede North Local Government Area of Osun. Population of the study was 690 students from five (5) (SSS) in Ede North Local Government Area of Osun State, namely: Timi Agbale Grammar School; C.A.C. Grammar School; Muslim Grammar School; Command Day Secondary School; and Mapo Arogun Comprehensive High School. Simple random sampling technique was adopted to draw a sample of 300 students for the study and 300 copies of the questionnaire were distributed while 289 (96.33%) copies were returned. Findings showed low level of Internet usage, attributed to nonavailability of computers in most of the schools studied, except the Command Day Secondary School with 154 (53.29%) students across the five secondary schools use the Internet and 135 (46.72%) do not use the Internet . The study also revealed that majority of the students (79.22%) use the Internet to their advantage in general, while 20.78% responded on its adverse usage. The study further brought to light that the use of Internet has both positive and negative effects on the youths, as 70.13% of the respondents agreed that its use has positive effects on their academics while 29.87% agreed to the contrary. The paper concludes that low Internet usage was recorded among the secondary school students in Ede North Local Government. It was recommended, among others, that attention be paid to the procurement of computers and installation of internet facilities for the teaching of computer education as ICT is essential in keeping with the dynamics of social change and demands in education.